Development of a Culturally Integrated Ecosport Tourism Model Based on Tsunami Heritage in Aceh Province - Syahrinursaifi, Syahrinursaifi; Musran, Musran; Kurniawan, Erizal; Husaini, Husaini; Saputro, Yulianto Dwi (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2025)
This study originates from the underdeveloped management of tourist attractions in Aceh, which has not been optimized to its full potential. Aceh currently requires a marketable tourism model that leaves a lasting impression on visitors. One promising alternative is ecosport tourism, an integration of sports activities and tourism that fosters interaction between tourists and local destinations. The objective of this study is to develop a tourism model that addresses the needs of the sports sector in Aceh. This research employs a qualitative research and development (R&D) approach, using interviews, documentation, and field observations as data collection methods. The data were analysed through the identification and description of tourism sites, as well as the formulation of appropriate ecosport models. The study findings reveal three potential ecosport tourism models based on regional characteristics: (1) walking or trekking in Banda Aceh, with six tourism stops featuring tsunami heritage sites; (2) cycling in Aceh Besar, covering seven cultural and natural destinations; and (3) a mixed-sport model in Central Aceh, which includes swimming, paragliding, rafting, and horseback riding. Expert validation results indicated a content validity score of 92%, categorized as